2018
DOI: 10.1080/14756366.2018.1481404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray structure, in silico calculation, and carbonic anhydrase inhibitory properties of benzylimidazole metal complexes

Abstract: Three coordination compounds of formula {M(bmim)2Cl2} were synthetised (M = Co, Zn, and Hg) and fully characterised. Each complex incorporates 1-benzyl-2-methylimidazole (bmim) as ligand. The coordination polyhedron around the metal center for all complexes has a quasi-regular tetragonal geometry. Density functional theory calculations were carried out on the title compounds and as well on hypothetical complexes (Cu, Ni), in order to elucidate their electronic and molecular structure. The calculations reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The initial geometries of the synthesized compounds were taken from the Xray structures and were optimized by the DFT method to minimize energy using the GAUSSIAN-09 program [49]. In the case of the two rhenium compounds, DFT methods were used to give correct results for transition metal-containing systems [50]. Among the different density function methods, the hybrid B3LYP [51,52] proves to be a suitable choice for fac-Re(CO) 3 complexes specifically.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…The initial geometries of the synthesized compounds were taken from the Xray structures and were optimized by the DFT method to minimize energy using the GAUSSIAN-09 program [49]. In the case of the two rhenium compounds, DFT methods were used to give correct results for transition metal-containing systems [50]. Among the different density function methods, the hybrid B3LYP [51,52] proves to be a suitable choice for fac-Re(CO) 3 complexes specifically.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%
“…23 Tin metal complexes have been shown to induce caspase dependent apoptosis in cancer cells. 24 Metal complexes have largely been employed in medicinal chemistry as bioactive molecules which are effective carbonic anhydrase inhibitors, 25 antimicrobial, 26 and anticancer 27 agents. Various metals can be used to achieve libraries of these metallodrugs with structural diversities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] D'Ambrosio et al [ 38 ] reported the first structural information on the CA inhibition mechanism of catechol, showing that they adopt a peculiar binding mode to the enzyme active site, involving the zinc‐bound water molecule and the “deep water.” Besides organic compounds, some of the organometallic complex structures were also investigated for their inhibition potential against hCAs. Bouchouit et al, [ 39 ] Alyar and Adem, [ 40 ] and Ul‐Hassan et al [ 41 ] reported some metal complexes with organic structures for hCAs inhibitions. Ghiasi and her co‐workers also investigated the theoretical modeling of the complex structure of CA and ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Besides organic compounds, some of the organometallic complex structures were also investigated for their inhibition potential against hCAs. Bouchouit et al, [39] Alyar and Adem, [40] and Ul-Hassan et al [41] reported some metal complexes with organic structures for hCAs inhibitions. Ghiasi and her co-workers also investigated the theoretical modeling of the complex structure of CA and ligands.…”
mentioning
confidence: 99%